FUNGSI MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MTS NURUL HUDA SUKARAJA KECAMATAN BUAY MADANG KABUPATEN OGAN KOMERING ULU TIMUR - Nurkholis; Tamyis; Abdul Roni (UNISAN JURNAL, 2023)
As a manager of a Madrasah in addition to being an educator, the Principal is a top manager, namely managing Madrasas so that the full potential of Madrasas functions optimally. MI head management Bahrul Ulum uses the POAC function. However, teacher performance has not been maximized either in planning, implementation or evaluation. The problems in this study are (1) How the Headmaster’s management functions in improving the performance of MTs Nurul Huda Sukaraja Kecamatan Buay Madang Kabupaten OKU Timurteachers (2) What factors support and hinder the performance of MTs Nurul Huda Sukaraja Kecamatan Buay Madang Kabupaten OKU Timurteachers. The purpose of this study is to find out and describe about: 1) The principal’s management function in improving the performance of MTs Nurul Huda Sukaraja Kecamatan Buay Madang Kabupaten OKU Timurteachers. 2) Supporting factors and factors inhibiting the performance of MTs Nurul Huda Sukaraja Kecamatan Buay Madang Kabupaten OKU Timurteachers, Punggur District, Central Lampung district. This type of research is a qualitative and descriptive study, a study that illustrates the principal’s management function in improving the performance of MTs Nurul Huda Sukaraja Kecamatan Buay Madang Kabupaten OKU Timurteachers, Punggur District, Central Lampung district. Sources of data in this study are: (1) Primary data, consisting of Madrasah heads, Madrasah deputy heads, staff / employees, teachers; (2) Secondary data, obtained from library research and documentation. Data collection methods in this study were observation, interviews, and documentation. Data analysis method is done by processing data (selecting, classifying, summarizing results, and making data reduction).The results showed that the Principal had carried out the stages of management functions well from the planning to the supervision stages (Controling), but in practice it sometimes encountered obstacles, this was due to the not fulfilling professional teachers, the lack of infrastructure, there were still teachers who did not understand the lesson plan and are reluctant to make lesson plans, the lack of teacher awareness of discipline in teaching. The teacher’s ability in evaluating learning is not yet comprehensive, some still lead to the cognitive and psychomotor aspects being overlooked. Bahrul Ulum includes: sincerity of work, appreciation of teachers and factors inhibiting teacher performance including: minimal facilities and infrastructure.